Stability analysis of random systems with Markovian switching and its application. Issue 1 (January 2016) - Jiao, Ticao; Lu, Junwei; Li, Yongmin; Chu, Yuming; Xu, Shengyuan
Abstract: This paper aims to study a class of Markovian switching random systems with stochastic processes whose α -order moments ( α > 1 ) are finite. Compared with the existing results, the existence and uniqueness of solutions to random systems with Markovian switching is not given as a priori information but guaranteed under some general conditions. The corresponding criteria on noise-to-state stability and boundedness are presented by employing the Lyapunov method. Finally, based on the derived results, a design procedure of state-feedback tracking control is proposed, which is illustrated through two examples.